UTILIZATION OF AUDIOVISUAL MEDIA AND SNOWBALL THROWING METHOD TO IMPROVEMENT BIOLOGICAL LEARNING PROCESS ON THE ELEVENTH YEARS OF NATURAL SCIENCE 2 IN BATIK I SURAKARTA SENIOR HIGH SCHOOL THE YEAR EDUCATED OF 2007/2008 - Santosa, Slamet; Nugraheni P., Tri (Prosiding Seminar Biologi, 2009)
Abstrak Purpose of this research is to improvement biological learning process at human nervous and sense system materials by using audiovisual media and Snowball Throwing method on the eleventh years of natural science 2 in Batik I Surakarta senior high school the year educated of 2007/2008. Kind of this research is Classroom Action Research (PTK), which is conducted in 2 cycles. The action research includes: identifying, planning, acting, observing, and reflecting. Subject of this research is student of eleventh years of natural science 2 in Batik I Surakarta senior hight school the year educated of 2007/2008. Technique collecting data are observational technique by using observational document, questionnaire, interview, document analysis, and test. Technique analyzing data in this research use descriptive qualitative method. The result of the research show that utilization of audiovisual media and Snowball Throwing method can improvement biological learning process which is characterized with the increases of student's result. The result of observatioru student's learning process is increases of active students from first cycle to second cycle are 16,275%. The result of average student's cognitive study increases 10,5 from first cycle to second cycle. The result of student's affective study increases 5,58% from first cycle to second cycle. Based on the research can be concluded that: utilization of audiovisual media and Snowball Throwing rnethod can improvement biological learning process on the eleventh years of natural science 2 in Batik I Surakarta senior high school the year educated of 2007/2008. Key word: Snowball Throwing method, audiovisual media, classroom action research, process of learning, descriptive qualitative.